2022
DOI: 10.3390/ijms232012458
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Using an Autogenous Tendon Graft by Injecting Bone Marrow Aspirate in a Rabbit Meniscectomy Model

Abstract: Bone marrow aspirate (BMA) is an excellent source of cells and growth factors and has been used successfully for bone, cartilage, and soft-tissue healing. This study aimed to investigate the histological and biomechanical properties of autogenous tendon graft by injecting BMA and its protective effect against degenerative changes in a rabbit model of meniscal defects. Adult white rabbits were divided into untreated, tendon, and tendon + BMA groups, and meniscal defects were created in the knees. The tendon gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In 2022, Hiroaki Nakamura published a study investigating the use of bone marrow aspirate (BMA) injection to enhance the histological properties of autologous tendon as a meniscus graft [ 20 ]. And, they concluded that the autogenous tendon grafts by injecting BMA improved the histologic score of the regenerated meniscal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Hiroaki Nakamura published a study investigating the use of bone marrow aspirate (BMA) injection to enhance the histological properties of autologous tendon as a meniscus graft [ 20 ]. And, they concluded that the autogenous tendon grafts by injecting BMA improved the histologic score of the regenerated meniscal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using power analysis ( β = 0.1 and α = 0.05) assuming a 2.5 difference in mean ICRS scores and a standard deviation of 1, as described in a previous study [7]. SPSS (version 24.0) was used for statistical analysis and all data were expressed as mean ± standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…Although the iliac bone, scapula, femur, rib, and radius have been used successfully for upper extremity reconstruction, the fibula has become the most appropriate choice for upper extremity reconstruction [ 7 ]. Vascular fibula transfer will be a more appropriate option for previous surgery in bone defects larger than 6 cm or for defective pseudoarthrosis with impaired blood supply secondary to infection [ 8 ]. With the vascular fibula graft, many surgeons have achieved significant union within an average of four to six months [ 9 ].…”
Section: Introductionmentioning
confidence: 99%